The estimated glomerular filtration rate was U-shaped associated with abdominal aortic calcification in US adults: findings from NHANES 2013–2014 - Wang, Liangliang; Li, Qiang; Su, Baolin; Zhang, En; Zhang, Shu; Tu, Haitao; Zhang, Liangyou; Wang, Chao; Chen, Gangyi (Frontiers in Cardiovascular Medicine, 2023)
Objectives The high incidence of abdominal aortic calcification (AAC) is well-documented in individuals with severe renal function decline. However, there is limited research on the historical relationship between estimated glomerular filtration rate (eGFR) and the risk of AAC occurrence in the general population undergoing routine medical examinations. The main objective of this study was to investigate the historical relationship between eGFR and AAC in the general population of the United States. Methods We performed a cross-sectional study using the National Health and Nutrition Examination Survey 2013–2014 database. Weighted multivariate linear regression models were used to estimate the associations of eGFR with AAC score. Smooth curve fitting and two-piecewise linear regression were employed to explore the potential non-linear relationship. Results A total of 2,978 participant (48.22% were male) aged 40–80 years were included in this study. The fully-adjusted model demonstrated a negative correlation between eGFR and AAC score (β = −0.015, 95% CI: −0.023 to −0.006). However, when applying the smooth curve fitting method, a U-shaped relationship was identified, and the inflection point was calculated at 76.43 ml/min/1.73 m2 using the two-piecewise linear regression model. Conclusions There was a U-shaped association between eGFR and AAC score in general US adults, with an inflection point at about 76.43 ml/min/1.73 m2.